THE EFFECT OF FLASH CARD MEDIA USE ON EARLY CHILDREN'S NUMERIC ABILITY AT NURUL AMIN PARAMAYAN PAUD, SERANG REGENCY - Mila Karmila; Umalihayati; Yolanda Pahrul; Amat Hidayat; Siti Kholifah (Cakrawala Pedagogik, 2025)
This study was conducted to address the research questions regarding how the implementation of clean and healthy living behavior (PHBS) can be promoted through physical activities in children aged 5–6 years at KB PAUD Al-Hidayah, Serang Regency. The purpose of this study is to examine the effectiveness of physical activities in improving PHBS among early childhood students. The research employed a Classroom Action Research (CAR) method consisting of two cycles, each including the stages of planning, action, observation, and reflection. The subjects of this study were 9 children aged 5–6 years. Data collection techniques included observation, documentation, and field notes. The results showed a noticeable improvement in PHBS after the children participated in physical activities. The children began to develop habits such as washing hands with soap before meals, throwing trash in the designated place, and maintaining body hygiene after activities. These improvements were significantly evident in each cycle, as indicated by the observation sheets. The study concludes that enjoyable and structured physical activities can serve as an effective medium for instilling PHBS in early childhood. It is recommended that teachers integrate physical activities into daily routines and collaborate with parents to reinforce PHBS habits at home. Furthermore, health authorities are encouraged to support this program.